The mediating effect of employee’s job satisfaction on the relationship between transformational leadership style and employee well-being among Malaysian academics - Tengku Mohd Azzman, Tengku Siti Aisha (University Putra Malaysia, 2020)
An effective leadership style might be a key variable in ensuring that employees thrive and remain happy at the workplace, in addition to working experience. However, an employee’s well-being may also depend on their working experience, and if they are able to achieve an optimal level of job satisfaction. Thus, this study aims to identify both organisation-specific and employee-specific factors that would influence employee well-being among academics from a higher education institution (HEI) in Malaysia. Specifically, it is predicted that transformational leadership style would positively predict employee well-being, while working experience would positively influence employee wellbeing. We also propose that job satisfaction would serve as a mediator in the relationship between transformational leadership style and employee well-being. Using a Google form, an online survey questionnaire was distributed among academic staff from a Malaysian university to determine the relationship between transformational leadership style, working experience, job satisfaction and employee well-being (N = 218). Overall, findings indicate that job satisfaction partially mediates the relationship between transformational leadership style and employee well-being. The impact of these findings on the influence of transformational leadership style on organisational outcomes, from the context of higher education institution, will be discussed.